Exciton relaxation in KBr and CaF2 at low temperature: molecular dynamics study: Electronically Induced Phenomena - Song, K.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We report here recent study of molecular dynamics simulation of exciton relaxation in several ionic crystals at low temperature. Both the lowest energy spin triplet and some of the low lying hole excited states are allowed to relax in view of studying the radiation defect formation channels. The previously used semi-classical program has been modified to implement the solution of Newton’s equations with 0.48 fs time step. The relaxation of an exciton localized on a single site (as Br0 + e, or F0 + e, respectively) is studied at 10 K in KBr and in CaF2. In KBr the triplet self-trapped exciton leads to separated Frenkel pair in about 1–2 ps, followed by slow oscillation of the hole center along the (110) axis. The defect pair created is separated by about 10 Å (third nearest neighbor). In CaF2, the relaxation reaches the geometry of the nearest Frenkel pair, with the hole center oriented along a (111) axis in about 0.3 ps at 10 K. However, at 80 K the system can undergo further relaxation into a slightly more distant defect pairs. When the hole is excited to higher levels, the molecule bond of the hole center undergoes violent oscillations. In KBr, the hole center is found to form in the second nearest neighbor position within about 0.5 ps. The species formed are, however, different from the well known primary radiation defects. Similar process is also observed in CaF2.